PENGARUH STABILITAS SUASANA HATI (MOOD) DAN TEMAN SEBAYA TERHADAP PEMBELIAN IMPULSIF - , DEVI MIFTIANA MILADANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Shopping is not only to satisfy daily needs, but also to satisfy the social and psychological needs. Marketer and producent can find the how to interested consumer to buy. This research aims to describe the influence of mood stability and peer influence on impulsive buying. Subjects in this research ware 250 respondents selected by incidental sampling technique. Which anyone who happened to be found in the research place and meet the characteristic of research subjects. This research aims to quantitative method and measured using three instruments namely the scale of impulsive buying scale, mood and peers scale. The three scales were analyzed using multiple regression analysis. The result showed that mood stability variable and peers variable has a significant relationship with the impulse buying variable. With the effective contribution value of R Square = 0, 263, F = 44.009, and the value of R = 0.513, wich means that impulse buying influencing predictor variable (stability mood and peers variable) amounted to 26.3%.